Consumer preferences for green power in Mexico. (1st January 2014) - Reyes-Mercado, Pável; ,
Mexico has an abundant supply of renewable energy resources but little is known about the consumers' preferences for green power consumption. This paper investigates households' preferences for adoption of green power technologies in Central Mexico. Using a structured questionnaire, we presented a green power purchase scenario to elicit consumers' buying intention. We estimate the buying intention for specific adoption of water solar boilers as it is a critical equipment to deploy in the study region. We find some evidence that buying intention is largely influenced by the affordability of equipment, even if such equipment's energy is not green. Equipment availability, relative advantage, and perceived value of utilisation were found to influence buying intention positively. Our results shed light on buying consumers' intentions and the current green power options, and offer practical insight into Mexican household preferences on how to support further deployments of green power.